2005
DOI: 10.1055/s-2004-861562
|View full text |Cite
|
Sign up to set email alerts
|

Biopsy of the Transplanted Kidney

Abstract: This article describes the current state-of-the-art technique of percutaneous transplant renal biopsy. A brief overview of the history of transplant renal biopsy is given. The indications and contraindications are discussed, including pre- and postprocedure patient management. The technique of the procedure and the devices that are available in the market are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 35 publications
1
33
0
Order By: Relevance
“…MicroRNAs (miRNAs) play an important role in many biological processes, while they could regulate the expression of genes implicated in immune response [20,27,28]. Furthermore, some studies showed that miR-142, miR-155, miR-223, miR-150 and miR-144 are highly specific for hematopoietic cell lineage [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MicroRNAs (miRNAs) play an important role in many biological processes, while they could regulate the expression of genes implicated in immune response [20,27,28]. Furthermore, some studies showed that miR-142, miR-155, miR-223, miR-150 and miR-144 are highly specific for hematopoietic cell lineage [21].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, tissue biopsy is considered as a gold standard for diagnosis of allograft rejection [10]; however, it is highly invasive and requires risky procedures along with variation in reports of renal biopsies between pathologists [11,12]. The lack of non-invasive, accurate and specific diagnostic assays for graft rejection is a major difficulty in the management of renal transplant recipients [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…A tangential approach at either the upper or lower pole of the allograft yields the largest biopsy area within the renal cortex and avoids major intra-or extrarenal vessels (17,18). The needle track within the kidney should traverse only the renal cortex.…”
Section: Percutaneous Renal Transplant Biopsymentioning
confidence: 99%
“…The reported prevalence of complications including macroscopic hematuria ranges between 0.06% and 13% (18). Macroscopic hematuria is reported to occur in 5%-8% of patients (20,21).…”
Section: Percutaneous Renal Transplant Biopsymentioning
confidence: 99%
“…8 Life-threatening complications occur in less than 0.1%. 9e12 Transplant renal biopsy seems to carry a lower complication rate than native renal biopsy, 13 but there are fewer data on renal transplant biopsies. Bleeding complications can usually be managed with bed rest and blood product support if required.…”
Section: Renal Biopsy Complicationsmentioning
confidence: 99%